A comparison of mortality-related risk factors of COVID-19, SARS, and MERS: A systematic review and meta-analysis. Issue 4 (October 2020) - Lu, Lvliang; Zhong, Wenyu; Bian, Ziwei; Li, Zhiming; Zhang, Ke; Liang, Boxuan; Zhong, Yizhou; Hu, Manjiang; Lin, Li; Liu, Jun; Lin, Xi; Huang, Yuji; et al.
Highlights: COVID-19 mortality risk factors were similar to those of SARS and MERS. Advanced age, hypertension, diabetes, chronic lung disease, increased LDH, CRP, neutrophils and BUN and decreased albumin were positively correlated with COVID-19 mortality. The laboratory indicators of poor outcomes with the highest degrees of difference were similar among the three coronavirus diseases. Low lymphocyte subtype counts might be a factor in COVID-19 mortality. Summary: Objective: Coronavirus Disease 2019 (COVID-19) is a pandemic. This systematic review compares mortality risk factors including clinical, demographic and laboratory features of COVID-19, Severe Acute Respiratory Syndrome (SARS) and Middle East Respiratory Syndrome (MERS). The aim is to provide new strategies for COVID-19 prevention and treatment. Methods: We performed a systematic review with meta-analysis, using five databases to compare the predictors of death for COVID-19, SARS and MERS. A random-effects model meta-analysis calculated odds ratios (OR) and 95% confidence intervals (95% CI). Results: 845 articles up through 11/4/2020 were retrieved, but only 28 studies were included in this meta-analysis. The results showed that males had a higher likelihood of death than females (OR = 1.82, 95% CI 1.56–2.13). Age (OR = 7.86, 95% CI 5.46–11.29), diabetes comorbidity (OR = 3.73, 95% CI 2.35–5.90), chronic lung disease (OR = 3.43, 95% CI 1.80–6.52) and hypertension (OR = 3.38, 95% CI 2.45–4.67) were the mortality risk factors. The laboratory indicators lactic dehydrogenase (OR = 37.52, 95% CI 24.68–57.03), C-reactive protein (OR = 12.11, 95% CI 5.24–27.98), and neutrophils (OR = 17.56, 95% CI 10.67–28.90) had stronger correlations with COVID-19 mortality than with SARS or MERS mortality. Consolidation and ground-glass opacity imaging features were similar among COVID-19, SARS, and MERS patients. Conclusions: COVID-19′s mortality factors are similar to those of SARS and MERS. Age and laboratory indicators could be effective predictors of COVID-19 mortality outcomes.